Optimization of Self-Nanoemulsifying Drug Delivery System Combining Red Ginger and Aromatic Ginger Extracts to Improve Solubilization and Stability - Linda Hindiana; Retno Widyowati; Sukardiman (Universitas Airlangga, 2025)
Background: Red ginger (Zingiber officinale var. rubrum) and aromatic ginger (Kaempferia galanga L.) are traditional Indonesian medicinal plants with proven pharmacological activity, but their poor aqueous solubility requires formulation strategies to enhance solubilization and physical stability. Objective: This study aimed to optimize and evaluate a Self-Nanoemulsifying Drug Delivery System (SNEDDS) combining red ginger and aromatic ginger. Methods: The optimization was conducted by varying the oil-to-Smix ratio and extract concentration, while the internal Smix composition (Tween 80: PEG 400 = 1:2.8 w/w) remained constant to isolate the effect of oil–surfactant proportion. Virgin coconut oil (VCO), Tween 80, and PEG 400 were used as the oil phase, surfactant, and co-surfactant, respectively. Three formulas were prepared based on oil-to-Smix (w/w): Formula A (1:4.68, 500 mg extract), Formula B (1:10.6, 500 mg extract), and Formula C (1:10.6, 460 mg extract). Physical characterization included visual observation, centrifugation, particle size, polydispersity index (PDI), and transmittance before and after thermodynamic stability tests. Results: Formula A was unstable and exhibited precipitation. Before stability testing, Formula C showed improved dispersion, with a 41.5% reduction in droplet size and a 79.9% decrease in PDI relative to Formula B. After stability testing, Formula C demonstrated markedly better performance, including an 85.5% smaller droplet size, 81.4% lower PDI, and a 2.4% increase in transmittance compared with Formula B. These quantitative improvements indicated that Formula C exhibited more optimal solubilization capacity and physical stability. Conclusion: This study concludes that extract concentration and the oil-to-Smix ratio significantly influence SNEDDS characteristics, and Formula C represents the most favorable formulation for further development.